VD_FINDINFO PP 22/15 - 34/2016 vom 7. November 2016 - VD Tribunal cantonal (2016)
PRÉVOYANCE PROFESSIONNELLE, RENTE DE SURVIVANT, CONCUBINAGE | 18 LPP, 19 al. 2 LPP, 19 al. 3 LPP, 20 LPP, 20a LPP, 73 LPP